Pengaruh CAR, LDR, BOPO, NIM, dan Inflasi terhadap ROA Bank Terdaftar BEI Tahun 2022-2024 - Nanda, Fransiska Natalia; Trimeiningrum, Eny (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2026)
The banking sector plays a strategic role in maintaining national financial system stability and contributes significantly to overall economic growth. Therefore, bank profitability serves as a key indicator for evaluating banking performance. However, previous studies examining the determinants of return on assets (ROA) have reported inconsistent findings, particularly during the post–COVID-19 pandemic period. This study aims to analyze the effects of the capital adequacy ratio (CAR), loan to deposit ratio (LDR), operating expenses to operating income (BOPO), net interest margin (NIM), and inflation on ROA. The analysis focuses on conventional banks listed on the Indonesia Stock Exchange during the 2022–2024 period. A quantitative approach is employed, using secondary data obtained from banks’ annual financial statements and national inflation data. Multiple linear regression analysis is applied in this study. Prior to hypothesis testing, classical assumption tests are conducted, including tests for normality, multicollinearity, autocorrelation, and heteroskedasticity. The results indicate that, simultaneously, CAR, LDR, BOPO, NIM, and inflation have a significant effect on ROA. The Adjusted R-squared value of 0.764 indicates that 76.4% of the variation in ROA can be explained by these variables. Partially, BOPO has a negative and significant effect on ROA, while CAR, LDR, NIM, and inflation do not show a significant effect. These findings emphasize that operational efficiency is the primary determinant of banking profitability in Indonesia during the post-pandemic economic recovery period. Moreover, this study provides up-to-date empirical evidence that contributes to the literature on banking and financial performance.